2
$\begingroup$

Suppose we have relation $$z^2 + az + b=0 $$ where $a$ and $b$ are real and roots of this equation $z_1$ and $z_2$ form equilateral triangle with origin then what could be relation between $a$ and $b$ ? I simply applied quadratic formula in equation $$ z = \frac{-a \pm \sqrt{a^2 -4b}}{2} $$ now since it forms equilateral triangle with origin so $$|z_1| =|z_2|$$ applying which $$( \frac{-a + \sqrt{a^2 -4b}}{2})^2= (\frac{-a - \sqrt{a^2 -4b}}{2})^2$$ I arrived at $$a^2 = 4b$$ but my answer is incorrect , why?

$\endgroup$
  • $\begingroup$ Are you given that $a$ and $b$ are real? $\endgroup$ – MJD Dec 5 '14 at 14:23
  • $\begingroup$ Yes they are real $\endgroup$ – Tesla Dec 5 '14 at 14:24
  • $\begingroup$ It's hard to say what you did wrong, because you didn't show us your mistake. You're right that $z=\frac{-a\pm\sqrt{a^2-4b}}2$. Butyou don't say how you got from there to $a^2=4b$. $\endgroup$ – MJD Dec 5 '14 at 14:27
  • $\begingroup$ Okay i have now edited my steps $\endgroup$ – Tesla Dec 5 '14 at 14:32
  • $\begingroup$ The problem here is that $|z_1| = |z_2|$ is true whether or not the roots form an equilateral triangle; it is true whenever $z_1$ and $z_2$ are roots of the same quadratic, because the two roots are always conjugate. But the equilateral triangle condition is stricter. $\endgroup$ – MJD Dec 5 '14 at 14:34
1
$\begingroup$

Hint :

$z_1,z_2$ are complex numbers $$(z-z_1)(z-z_2)=z^2+az+b$$ $$z_1+z_2=-a$$

$$z_1z_2=b$$

Because of equal triangle, We know that $$z_1=M e^{i \alpha }$$ $$z_2=M e^{i (\alpha+ \pi /3) }$$ Thus you can use a relation between two complex numbers.

$$z_2/z_1=e^{i \pi /3}= \frac{ 1}{2}+i \frac{ \sqrt3}{2} $$

enter image description here

$\endgroup$
  • 2
    $\begingroup$ That picture is very misleading, because $z_1$ and $z_2$ are conjugate. $\endgroup$ – MJD Dec 5 '14 at 14:49
2
$\begingroup$

Hint; The triangle in the complex plane whose verticies are the origin and the points $z_{1}$ and $z_{2}$ is equalateral if and only if \begin{equation} z_{1}+z_{2} = z_{1}z_{2} \end{equation} (Further hint: The reasoning behind this is that the distance from the origin to $z_{1}$ is $\sqrt{z_{1}\bar{z_{1}}}$ etc...)

$\endgroup$
  • $\begingroup$ Suppose $z_1=\frac{1}{2}+\frac{\sqrt{3}}{2}i$ and $z_2=1$. Then the right hand side is $z_1z_2=z_1=\frac{1}{2}+\frac{\sqrt{3}}{2}i$. That's not equal to the left hand side $z_1+z_2=\frac{3}{2}+\frac{\sqrt{3}}{2}i$. $\endgroup$ – khalatnikov Oct 19 '18 at 6:12

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.